The Effect Of Ict Integration In The Use Of Inquiry Method On Pre-Service Teachers’ Achievement In Social Studies (Citizenship) Education In Nigerian Colleges Of Education - Alhaji Garba, Sani (2013)
Ilham untuk kajian ini tercetus daripada kebimbangan terhadap kurangnya minat dan penggunaan ICT dalam amalan pendidikan oleh guru-guru di sekolah Nigeria.